A General One‐Pot Synthesis of 2H‐Indazoles Using an Organophosphorus–Silane System. Issue 36 (6th June 2018) - Schoene, Jens; Bel Abed, Hassen; Schmieder, Peter; Christmann, Mathias; Nazaré, Marc
Abstract: A simple and direct approach for the regioselective construction of the privileged 2 H ‐indazole scaffold is described. The developed one‐pot strategy involves phospholene‐mediated N−N bond formation to access 2 H ‐indazoles. The amount of organophosphorus reagent was minimized by recycling the phospholene oxide with organosilane reductants. Starting from functionalized 2‐nitrobenzaldehydes and primary amines, a mild reductive cyclization, involving the use of commercially available phospholene oxide and silanes, delivered a wide variety of substituted 2 H ‐indazoles in good to excellent yields. Abstract : It's been a privilege : A simple mix‐and‐heat procedure enables rapid access to 2 H ‐indazoles as privileged scaffolds from 2‐nitrobenzaldehydes and primary amines by using a commercially available organophosphorus/silane system. Using this methodology, a library of 65 2 H ‐indazole derivatives carrying a broad range of substitution patterns is synthesized.